TEACHERS' PEDAGOGICAL BELIEFS AND TEACHING STYLES IN TEACHING ENGLISH AT UNIVERSITY LEVEL - Armin, Diah Safithri (2017)
The teachers should have the pedagogical beliefs in their study where these beliefs act as the filter and the guide for the teachers' decision and teaching styles in the teaching-learning process. Indonesian curriculum policy adapted the beliefs that focus on the students as the central of the learning process to create an active and meaningful learning process. However, most of the time the teachers are authoritative in managing the teaching-learning process and become the central of the learning process, while the students receive the knowledge passively. In response to this issue, the present study was conducted to find out the teachers' pedagogical beliefs and teaching styles at a university in Indonesia. The participants of this study were three English teachers who have been chosen based on their teaching skill. This study was basic interpretative qualitative study and the data were collected through closed-ended questionnaire, observation checklist, and field note. The data were analyzed by coding the data, summarizing the data, and looking for the point of the teachers' pedagogical beliefs and teaching styles. The result of data analysis showed that the teachers believed in teaching as a process of transmitting and constructing knowledge. They also believed in student-centered approach as their teaching pproach, while behaviourism and mentalism/rationalism as their view of language and language learning. According to the teachers, their roles as the teachers in the teaching-learning process were as the participant and director. Furthermore, the teachers used the combination of the teaching styles which belongs to constructivist and transmission beliefs. ----------- Dosen seharusnya memiliki keyakinan pedagogik dalam pengajarannya yang mana keyakinan ini berperan sebagai penyaring dan petunjuk bagi keputusan tindakan dosen dan gaya mengajar dosen dalam proses belajar mengajar. Kebijakan kurikulum di Indonesia mengadaptasi beliefs yang memfokuskan siswa sebagai pusat pembelajaran untuk menciptakan sebuah proses belajar yang efektif dan bermakna. Akan tetapi, hampir sepanjang waktu dosen autoritatif dalam mengelola proses belajar mengajar dan menjadikan dirinya sebagai pusat dari proses pembelajaran, sedangkan mahasiswa hanya menerima pengetahuan secara pasif. Sebagai respon terhadap isu ini, penelitian ini telah dilaksanakan untuk mengungkapkan keyakinan pedagogik dan gaya mengajar dosen di sebuah universitas di Indonesia. Partisipan penelitian ini adalah tiga orang dosen bahasa Inggris yang dipilih berdasarkan pada kemampuan mengajar sang dosen. Penelitian ini merupakan penelitian kualitatif interpretatif dasar dimana data dikumpulkan dengan menggunakan angket tertutup, lembar observasi, dan catatan lapangan. Data kemudian dianalisa melalui tiga tahap: mengkelompokkan data, menyimpulkan data, dan mencari poin penting keyakinan pedagogik dan gaya mengajar dosen. Hasil dari analisa data menunjukkan bahwa partisipan meyakini pembelajaran sebagai sebuah proses pengiriman dan pembangunan pengetahuan pada mahasiswa. Partisipan juga meyakini bahwa pendekatan pembelajaran yang mereka terapkan adalah student-centered, sementara pandangan bahasa dan pembelajaran bahasa yang mereka yakini adalah behaviourism dan mentalism/rationalism. Menurut partisipan, peranan mereka sebagai dosen dalam proses pembelajaran yakni sebagai partisipan dan direktur. Lebih lanjut, partisipan menerapkan kombinasi dari beberapa gaya mengajar yang merefleksikan keyakinan constructivist dan transmission.